Problems of installation water protective zones and coastal protective stripes - Rusina, N.; Lyulʹchyk, V.; Bida, P.; Kachanovsʹkyy, O.; Bulakevych, S.; Petrova, O. (Land Management, Cadastre and Land Monitoring, 2021)
The issue of establishing the boundaries of water protection and coastal stripes in Ukraine were examined in the article. The purpose of the study is to present the practical results of the formation the boundary delimiter of coastal protection stripes, based on scientific and methodological approaches to the development of land management projects for the establishment of coastal protection stripes and modern technologies in the area of geographic information system. Theoretical principles of establishing the boundaries of water protective zones and coastal protective stripes on water resources are analyzed. Regulatory basic documents on the subject of use in the establishment of water protection zones and coastal protection stripes have been explored. It is noted that the size of water protective zones and coastal protective stripes can be set in accordance with the provisions of the Land Code of Ukraine, and according to the especial projects in land management. It is suggested the procedure for establishing coastal and water protective zones is based on determining the hydrographic characteristics of water sites and morphological parameters of coastal areas using remote sensing data and geoinformation system and includes six steps: 1. Determination of morphometric parameters of water sites. 2. Obtaining relief data and its application 3.Determining the steepness of the slopes. 4. Construction of catchment areas and determination of surface effluent directions. 5. Creation of a buffer zone around water sites (construction of a protective stripe and a water protective zone). 6. Combining layers of informative maps for the final definition of boundaries. The use of the methodology is presented on a specific example, namely the pond in the village Gremyache, Rivne region. Methodology will provide a technical background for establishing and decision-making on the size of water protective zones and coastal protection stripes around water objects. One more aspect of the problem, solved by the methodology proposed in the article, involves informative supporting of decisions in a sphere of controlling water fund lands at the regional level as part of the planning measures for sustainable regions development and protection of water objects. Keywords: water protective zone, coastal protection belt, land management project, Earth remote sensing data of the Earth and geographic information system data, boundaries of the water protective zone and coastal protective stripe